Intradermal administration of the pneumococcal conjugate vaccine in mice results in lower antibody responses as compared to intramuscular administration. Issue 1 (4th January 2023) - Uijen, Rienke F.; van Beek, Lucille F.; van Opzeeland, Fred; Simonetti, Elles; van Selm, Saskia; Bonduelle, Olivia; Combadière, Behazine; Langereis, Jeroen D.; de Jonge, Marien I.
Abstract: Introduction: Several studies have shown that intradermal vaccination leads to improved immune responses. In addition, lowering vaccine doses will reduce costs and therefore potentially increase coverage. To determine whether intradermal delivery enhances the antibody responses against the 13-valent pneumococcal conjugate vaccine (PCV13), we compared intradermally and intramuscularly vaccinated mice. Methods: Mice were immunized with PCV13, either intradermally or intramuscularly and CFU-counts in the nasal tissue were determined three or seven days after intranasal colonization with a serotype 4 clinical strain. Antibody concentrations against all thirteen polysaccharides were measured in blood and mucosal samples using a fluorescent-bead-based multiplex immunoassay. Results: Antibody levels in both serum and mucosal samples were higher in the intramuscularly vaccinated group as compared to the intradermally vaccinated group. No protection against S. pneumoniae intranasal colonization was observed for either vaccination route. Conclusions: Intradermal vaccination was inferior to intramuscular immunization in inducing serotype-specific antibodies.